Influence of Temperature on Stacking Fault Energy and Creep Mechanism of a Single Crystal Nickel-based Superalloy. Issue 8 (August 2016) - Tian, Sugui; Zhu, Xinjie; Wu, Jing; Yu, Huichen; Shu, Delong; Qian, Benjiang
Abstract : The influence of temperatures on the stacking fault energies and deformation mechanism of a Re-containing single crystal nickel-based superalloy during creep at elevated temperatures was investigated by means of calculating the stacking fault energy of alloy, measuring creep properties and performing contrast analysis of dislocation configuration. The results show that the alloy at 760 °C possesses lower stacking fault energy, and the stacking fault of alloy increases with increasing temperature. The deformation mechanism of alloy during creep at 760 °C is γ′ phase sheared by <110> super-dislocations, which may be decomposed to form the configuration of Shockley partials plus super-lattice intrinsic stacking fault, while the deformation mechanism of alloy during creep at 1070 °C is the screw or edge super-dislocations shearing into the rafted γ′ phase. But during creep at 760 and 980 °C, some super-dislocations shearing into γ′ phase may cross-slip from the {111} to {100} planes to form the K–W locks with non-plane core structure, which may restrain the dislocations slipping to enhance the creep resistance of alloy at high temperature. The interaction between the Re and other elements may decrease the diffusion rate of atoms to improve the microstructure stability, which is thought to be the main reason why the K–W locks are to be kept in the Re-containing superalloy during creep at 980 °C.